Phyllantus acidus mediated combustion method synthesised yttria stabilized zirconia, its application as photocatalyst and antibacterial agent - H. Gujjaramma; B.S. Krishna; K. Gurushantha; S. Meena; G. Shobha; G.K. Raghu (Desalination and Water Treatment)
The ceramic material combines different functionalities such as good thermal stability, selective bulk oxygen mobility and high surface oxygen vacancy concentration are the most attracted research to opt for the 8 yttria stabilized zirconia nanomaterial. Nanocomposite 8 yttria stabilized zirconia powder (8YSZ) by bio-mediated combustion synthesis utilizing Phyllanthus acidus fuel. Cubic 8YSZ powder were discovered to be photocatalytic for the deterioration of anionic dyes. The synthesised NP's structural characteristics were assessed with the use of PXRD, UV-Vis, SEM, FTIR and TGA and DTA analyses. Additionally, by monitoring the AO7 coloring change in absorbance under the UV spectroscopy, the photo catalytic action of the 8YSZ on NPs dye has been shown. By tracking the drop in dye concentration relative to the initial dye concentration, the photodegradation of the AO7 organic dye was determined. Investigations have also been conducted on the impacts of operating parameters like pH, catalyst dosage. The present work stated that 8YSZ NP’s have a greater capability for deterioration when exposed to Visible radiation and investigated the antibacterial properties of high-quality ceramic material 8YSZ for use in dentistry.